A review on localization techniques in WSN - Kailas P. Tambe, Mr; G. Krishna Mohan, Dr (International Journal of Engineering and Technology, 2018)
Wireless Sensor network is a collection of small nodes which collect and send the data for processing. But data is meaningful when its location is known. The area of WSN localization is a developing rapidly by extensive research work. This location information can be achieved using different localization techniques in WSN. The location of events taken place can be determined by knowing the location of sensor nodes. This paper extensively reviews different localization techniques basic and improved one to localize nodes in WSN and also presents some parameter based comparative study. This study is valuable for better understanding of existing methods and improved ones, with the help of this can develop other advanced techniques.Â Â Â